Peripheral nerve injury alters excitatory synaptic transmission in lamina II of the rat dorsal horn - Kohno, T.; Moore, K. A; Baba, H.; Woolf, C. J (The Journal of physiology, 2003)
Using the blind whole cell patch-clamp recording technique, we investigated peripheral nerve injury-induced changes in excitatory synaptic transmission to neurones in lamina II of the dorsal horn. Partial (i.e. chronic constriction injury (CCI) and spared nerve injury (SNI)) and complete (i.e. sciatic nerve transection (SNT)) peripheral nerve injury altered the mean threshold intensity for eliciting A fibre-mediated EPSCs in lamina II neurones. Following SNT and CCI, EPSC threshold was significantly decreased, but following SNI, EPSC threshold was increased (naive: 32 Â± 2 Î¼A, SNT: 22 Â± 2 Î¼A, CCI: 23 Â± 2 Î¼A, SNI: 49 Â± 4 Î¼A; P < 0.01, Student's unpaired t test). Despite this disparity between models, dorsal root compound action potential recordings revealed no significant difference in the conduction velocity or activation threshold of AÎ² and AÎ´ fibres in naive, SNT, CCI and SNI rats. In addition to the changes in EPSC threshold, we also observed a shift in the distribution of EPSCs. In spinal cord slices from naive rats, polysynaptic AÎ² fibre-evoked EPSCs were observed in 24 % of lamina II neurones, monosynaptic AÎ´ fibre EPSCs were observed in 34 % and polysynaptic AÎ´ fibre EPSCs were observed in 7 %. Following SNT and CCI, the percentage of neurones with polysynaptic AÎ² fibre EPSCs increased to â¥ 65 % of the sampled population, while the percentage of neurones with monosynaptic AÎ´ fibre EPSCs decreased to < 10 %. The percentage of neurones with polysynaptic AÎ´ fibre EPSCs was unchanged. In contrast, following SNI, AÎ² fibre EPSCs decreased in incidence while the percentage of neurones with polysynaptic AÎ´ fibre EPSCs increased to 44 %. Similar to the other injury models, however, monosynaptic AÎ´ fibre EPSCs decreased in frequency following SNI. Thus, excitatory synaptic transmission is subject to divergent plasticity in different peripheral nerve injury models, reflecting the complexity of responses to different forms of deafferentation.